The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph20010425
|View full text |Cite
|
Sign up to set email alerts
|

Competence Development and Collaborative Climate as Antecedents of Job Performance, Job Commitment and Uncertainty: Validation of a Theoretical Model across Four Hospitals

Abstract: Knowledge is lacking regarding how organizational factors are associated with uncertainty in patient treatment. Thus, the aim of the current study was to investigate how competence development and collaborative climate relates to job performance and job commitment, and further whether job performance and job commitment relate to uncertainty. Additionally, we examined whether these associations differed between four different hospitals. We applied data from 6445 hospital workers who provided care to patients. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 72 publications
(88 reference statements)
2
5
1
Order By: Relevance
“…While previous literature has suggested a positive relationship between selfcompetence and organizational commitment (e.g. Battistelli et al, 2015) and that competencies lead to greater organizational commitment (Jensen et al, 2022), we verified that it was not found in our research. This finding suggests that the commitment of public servants may be influenced by specific characteristics of the Brazilian public sector, such as rigidity resulting from legislation and bureaucracy, as well as stability (Vieira et al, 2021).…”
Section: Discussion Of Resultscontrasting
confidence: 77%
See 4 more Smart Citations
“…While previous literature has suggested a positive relationship between selfcompetence and organizational commitment (e.g. Battistelli et al, 2015) and that competencies lead to greater organizational commitment (Jensen et al, 2022), we verified that it was not found in our research. This finding suggests that the commitment of public servants may be influenced by specific characteristics of the Brazilian public sector, such as rigidity resulting from legislation and bureaucracy, as well as stability (Vieira et al, 2021).…”
Section: Discussion Of Resultscontrasting
confidence: 77%
“…In this sense, Donkor (2021) highlight that competence produces individuals who expand economic growth in both the public and private spheres. Jensen et al (2022) demonstrated the existence of connections between competency development and organizational commitment. Organizational commitment and job satisfaction, in turn, indicate having a significant relationship with each other (Rodrigo et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations